THE ROLE OF GOVERNMENT FISCAL POLICY IN ENHANCING ECONOMIC GROWTH AND STATE REVENUE THROUGH THE TAXATION SYSTEM - Loso Judijanto; Mohd Syahrin; Hydzulkifli Bin Haji Hashim (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Fiscal policy is one of the main instruments used by the government to manage the national economy through the regulation of state expenditure and revenue, particularly from the taxation sector. This study aims to analyse the role of government fiscal policy in promoting economic growth and increasing state revenue, with a focus on the taxation system as the main instrument. The method used is a literature review of various scientific sources, official government reports, and international institution publications. The results of the study indicate that effective fiscal policy, through productive expenditure allocation and fair and efficient taxation policies, can stimulate economic activity, increase investment, strengthen purchasing power, and expand the tax base. The tax system plays a dual role, namely as a source of development funding and as a tool for regulating economic behaviour, which, if implemented appropriately, will create a multiplier effect on economic growth. However, challenges such as low tax compliance, tax avoidance and evasion practices, and limited administrative capacity need to be addressed immediately through structural reforms, system digitalisation, and strengthening the principles of fiscal justice. Therefore, synergy between sound fiscal policies and a modern and equitable tax system is key to achieving inclusive, sustainable economic growth that supports improved public welfare.